Development and validation of stability indicating spectrophotometric and HPTLC methods for determination of acemetacin - Naguib, Ibrahim Ahmed; Abdelaleem, Eglal Abdelhamid; Zaazaa, Hala Elsayed; Hussein, Essraa Abd ElWahab (European Journal of Chemistry, 2014)
Three simple and sensitive methods were developed for the determination of acemetacin (ACM) in presence of its degradation product, indomethacin (DEG). Several methods were evaluated and are presented. Method A was based on measuring the peak amplitude of the first derivative of the ratio spectra 1DD at 244 nm. In method B, mean centering of ratio spectra method (MCR) was applied, which depends on measuring the mean centered values of ratio spectra of ACM at 234 nm. Method C provided separation of ACM from its DEG on pre-activated silica gel 60F254 HPTLC plates using hexane:ethyl acetate:glacial acetic acid (6:4:0.3, v:v:v) as developing system followed by scanning at 254 nm. The suggested methods were validated in compliance with the International Conference on Harmonisation (ICH) guidelines and were successfully applied for quantification of ACM in its commercial capsule. The proposed methods were also statistically compared to a reported HPLC method with no significant difference in performance; indicating the ability of the proposed method to be reliable and suitable for routine analysis of drug product.